The role of the State on foreign direct investment regulation in China - PAULA CARVALHO; ISABELA NOGUEIRA (Brazilian Journal of Political Economy, 2023)
ABSTRACT This article intends to corroborate the argument advocated by heterodox economists such as Akyüz, Chang and Furtado that state regulation is crucial to extracting the possible benefits of foreign direct investment (FDI). We do so by analyzing the policies used by China since its opening to this type of investment in 1979. The article innovates by scrutinizing China’s major FDI laws, regulations and guidelines that compose the formal framework under which foreign-owned enterprises have operated in the country for almost 40 years. We then address the traditional view that China developed simply because it increasingly opened its market to foreign investment and adopted a foreign investment-led growth model. We argue that it was because of this strong regulation that FDI had such a positive effect, contributing to technological transfer and trade expansion, although not defining the ratio of capital accumulation.